2006
DOI: 10.1073/pnas.0511035103
|View full text |Cite
|
Sign up to set email alerts
|

Force-dependent chemical kinetics of disulfide bond reduction observed with single-molecule techniques

Abstract: The mechanism by which mechanical force regulates the kinetics of a chemical reaction is unknown. Here, we use single-molecule force-clamp spectroscopy and protein engineering to study the effect of force on the kinetics of thiol͞disulfide exchange. Reduction of disulfide bonds through the thiol͞disulfide exchange chemical reaction is crucial in regulating protein function and is known to occur in mechanically stressed proteins. We apply a constant stretching force to single engineered disulfide bonds and meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
372
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 328 publications
(390 citation statements)
references
References 47 publications
10
372
2
1
Order By: Relevance
“…Protein Expression and Purification-Preparation of (I27 SS ) 8 polyprotein was prepared as described previously (18,24) with a few differences. Two residues were mutated in the I27 module using a QuikChange site-directed mutagenesis kit (Stratagene) to engineer a buried intracellular disulfide bond.…”
Section: Methodsmentioning
confidence: 99%
“…Protein Expression and Purification-Preparation of (I27 SS ) 8 polyprotein was prepared as described previously (18,24) with a few differences. Two residues were mutated in the I27 module using a QuikChange site-directed mutagenesis kit (Stratagene) to engineer a buried intracellular disulfide bond.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, the Trx catalysis proceeds by the S N 2 reaction mechanism, 11,12 which requires that the disulfide bond and the sulfur atom of the enzyme align in the same direction forming a straight line. 15,25,29,30 Therefore, in order for the S N 2 reaction to proceed, the system must overcome a deformation energy barrier associated with the rotation of the disulfide bond with respect to the Trx grove. Simulations show 30 that the bond rotation causes a contraction of the I27 domain, and that the contraction is opposed by the pulling force.…”
Section: Deformation Model Of Enzyme Catalysis In the Presence Of Forcementioning
confidence: 99%
“…Recently, Fernandez and co-workers published a series of articles 15,25,29,30 reporting novel and unexpected results regarding the enzymatic dissociation of disulfide bonds subjected to external force. A number of different enzymes were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…These Ig domains are found in many adhesion and matrix proteins, and some cytoskeletal proteins also are reported to have at times an intact S-S bond (7). Wiita et al (5) engineered the well characterized titinIg27 domain to have a similar disulfide. Stretching such proteins by AFM had been done on wild-type Ig-cell adhesion molecules (CAMs) (8, 9) and had suggested that a one-dimensional version of Eq.…”
mentioning
confidence: 99%
“…Moreover, the log-dependence on force also fits the one-dimensional theory of bond extension, giving ⌬x* ϭ 0.34 Å for the engineered titin domain (5). Although Wiita et al (5) point out that it is not yet known how often any disulfide bond in vivo will be exposed to the force levels that they explored, it does seem likely that the sensitivity of any particular thiol͞disulfide exchange reaction to a pulling force will depend very specifically on the environment surrounding the bond. Temperature already has proven to strongly influence protein unfolding and refolding in AFM (11)(12)(13).…”
mentioning
confidence: 99%